Brodifacoum pharmacokinetics in acute human poisoning: implications for estimating duration of vitamin K therapy. Issue 1 (30th November 2021) - Nosal, Daniel G.; van Breemen, Richard B.; Haffner, John W.; Rubinstein, Israel; Feinstein, Douglas L.
Abstract: Standard of care follow-up therapy for patients poisoned by long-acting anticoagulant rodenticides (LAARs) is daily high-dose (up to 100 mg per day) oral vitamin K1 (VK1 ) for weeks to months to over a year. The availability of CLIA-certified quantitative testing for plasma LAAR concentrations can now assist health care providers in determining when to safely discontinue VK1 therapy. We present estimates of treatment duration required to reach safe concentrations (< =10ng/ml) using serial measurements of plasma brodifacoum (BDF, a potent LAAR) concentrations obtained from patients poisoned after inhaling synthetic cannabinoids containing BDF. We fit the data to zero-order (linear) and first-order (exponential) curves, the latter to account for enterohepatic circulation of BDF. The results show that estimates of therapy duration are significantly longer when exponential clearance is assumed. Accordingly, we recommend that plasma BDF concentrations be monitored simultaneously with international normalization ratio (INR) during follow-up of poisoned patients, and that concentrations be determined after VK1 therapy is discontinued to document persistence of safe concentrations.